Bridging the gap in cervical cancer screening for underserved communities: MCED and the promise of future technologies - Alshammari, Aya Hasan; Ishii, Hideshi; Hirotsu, Takaaki; Hatakeyama, Hideyuki; Morishita, Masayo; di Luccio, Eric (Frontiers in Oncology, 2024)
Cervical cancer screening is a critical public health measure, especially vital for underserved communities where disparities in access and outcomes are pronounced. Despite the life-saving potential of regular screening, numerous barriers—including geographical isolation, cultural and linguistic challenges, and socioeconomic factors—severely hinder accessibility for these populations. Multi-Cancer Early Detection (MCED) tests emerge as a potentially effective intervention, offering a less invasive, more accessible approach that could transform how screenings are conducted. This paper explores the existing challenges in traditional cervical cancer screening methods, the potential of MCED tests to address these barriers, and the implications of these technologies for global health equity. Through a comprehensive review, we highlight the need for culturally sensitive, tailored interventions and the importance of effectively overcoming logistical and financial difficulties to implement MCED tests. Despite the promise shown by MCED tests, the paper acknowledges significant implementation challenges, including cost, logistical obstacles, and the need for cultural acceptance and validation studies. This study emphasizes the necessity for equitable MCED test implementation strategies, highlighting the potential of these innovative technologies to advance global health equity in cervical cancer prevention